Hubungan Antara Minat Baca Dengan Hasil Belajar PPKn Peserta Didik Kelas 5 Sekolah Dasar Negeri 1 Gerung Utara Tahun Ajaran 2020 / 2021 - Hamzan Wadi; Ida Bagus Kade Gunayasa; Khairunnisa (Pendagogia: Jurnal Pendidikan Dasar, 2021)
Reading is the beginning of learning, without reading we cannot know anything because reading is opening a window to the world. The level of interest in reading has a relationship with learning outcomes. The formulation of the problem in this study, namely, is there a relationship between reading interest and PPKn learning outcomes for grade 5 students at SDN 1 Gerunng Utara for the 2020/2021 academic year. The purpose of this study is to examine the relationship between reading interest and Civics learning outcomes for grade 5 students at SDN 1 Gerung Utara for the 2020/2021 academic year. The type of research used is correlational research. The research sample was 68 5th grade students of SDN 1 Gerung Utara. Sampling using simple random sampling technique. Data collection techniques using a questionnaire / questionnaire and documentation. Hypothesis testing using the product moment test with the help of SPSS version 16. The results showed that the correlation between reading interest and PPKn learning outcomes was 0.952 with a correlation level of 0.236 (rcount 0.952 > rtable 0.236). This shows that there is a relationship between reading interest and PPKn learning outcomes for grade 5 students at SDN 1 Gerung Utara for the 2020/2021 Academic Year. The percentage of the relationship between reading interest and PPKn learning outcomes is 90.63%.